2019
DOI: 10.3892/or.2019.7248
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of FoxM1 by HIF‑1α mediates hypoxia‑induced EMT in prostate cancer

Abstract: Hypoxia is a tumorigenesis-related microenvironment change which usually occurs in the earliest stage of prostate cancer (PCa) development. Accumulating evidence has demonstrated that hypoxia/hypoxia-inducing factor (HIF) is involved in the induction of epithelial-mesenchymal transition (EMT) and increased metastatic potential in PCa. However, the mechanism by which hypoxia/HIF regulates EMT remains unclear. In the present study, we demonstrated the molecular mechanisms of hypoxia-induced EMT in PCa, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 65 publications
1
21
1
Order By: Relevance
“…In contrast, N-Cad as a mesenchymal cell-cell adhesion protein, as well as vimentin protein expression, are increased [41]. EMT is stimulated by various signals, including hypoxia, which was shown to prompted EMT in prostate cancer cells [22]. Here, our study also verified hypoxia insult caused a decrease of E-Cad protein expression, whereas an increase of N-Cad and vimentin protein expression.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…In contrast, N-Cad as a mesenchymal cell-cell adhesion protein, as well as vimentin protein expression, are increased [41]. EMT is stimulated by various signals, including hypoxia, which was shown to prompted EMT in prostate cancer cells [22]. Here, our study also verified hypoxia insult caused a decrease of E-Cad protein expression, whereas an increase of N-Cad and vimentin protein expression.…”
supporting
confidence: 77%
“…These results indicated that TRPM7 knockdown promoted the degradation of HIF-1α of androgen-independent prostate cancer cells in hypoxic conditions. HIF-1α is involved in EMT of prostate cancer cells [22]. Our western blot results showed that knockdown of HIF-1α inhibited EMT change of androgen-independent prostate cancer cells induced by hypoxia in both PC3 and DU145 cells.…”
Section: Trpm7 Knockdown Suppressed Hif-1α Proteinmentioning
confidence: 62%
See 1 more Smart Citation
“…HIF-1α may also act on some EMT transcription factors indirectly through FoxM1 signaling pathway in prostate cancer cell lines (76) and through PAFAH1B2 gene in pancreatic cancer (77). HIF-1α also facilitated the regulatory loop with integrin-linked kinase (ILK) to promote epithelial-mesenchymal transition in breast and prostate cancer cell lines (78).…”
Section: Hif-mediated Emtmentioning
confidence: 99%
“…It has been shown that growth factors, such as epidermal growth factor (EGF), transforming growth factorβ (TGF-β), and basic fibroblast growth factor (bFGF/FGF2) are also able to induce EMT (14,15). It has also recently reported that tumor microenvironment conditions such as hypoxia and acidosis can induce EMT (16,17).…”
Section: Introductionmentioning
confidence: 99%